Does the nature of the victimization–offending association fluctuate over the life course?: an examination of adolescence and early adulthood - Schreck, Christopher J. (Crime & delinquency, 2017)
Decades of criminological research has established that victimization is strongly connected with offending—this pattern is among the most durable in the criminological literature. However, there are plausible reasons to believe that under some theoretically defined conditions, the association can vary across the life course. Using 10 waves from the Pathways to Desistance data, which follow more than 1,300 youth from early adolescence into adulthood, we model within-individual change in the victimization–offending association as well as evaluate possible theoretical reasons for this change. Our results show that the influence of victimization on offending weakens as people age, although the association remains positive across the life course. The core substantive predictors, however, could not account for this temporal weakening of the association. We discuss the implications of these results for further theoretical development on offending.